1981
DOI: 10.1128/iai.32.3.1024-1027.1981
|View full text |Cite
|
Sign up to set email alerts
|

Specific Capsular Polysaccharide of Type 46 Streptococcus pneumoniae (American Type 73)

Abstract: The specific capsular polysaccharide of type 46 Streptococcus pneumoniae (American type 73) was isolated in pure form and shown to be a high-molecular-weight, glycosidically linked polymer composed of d -galactose (2 mol), N -acetyl- d -glucosamine (1 mol), N -acetyl- d -galactosamine (1 mol), and N -acetyl- l -fucosamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Most diseases caused by S. pneumoniae are due to approximately 20 types. For American and European vaccine recipients, polysaccharides specific for types 1,2,3,4,6,8,12,14,19,23,25,51, and 56 (American serotype numbers) are recommended (5). For recipients in Africa and Southwest Asia, types 45 and 46 (Danish serotype numbers; Danish serotypes 45 and 46 are American serotypes 72 and 73 of S. pneumoniae) are also recommended (5).…”
mentioning
confidence: 99%
“…Most diseases caused by S. pneumoniae are due to approximately 20 types. For American and European vaccine recipients, polysaccharides specific for types 1,2,3,4,6,8,12,14,19,23,25,51, and 56 (American serotype numbers) are recommended (5). For recipients in Africa and Southwest Asia, types 45 and 46 (Danish serotype numbers; Danish serotypes 45 and 46 are American serotypes 72 and 73 of S. pneumoniae) are also recommended (5).…”
mentioning
confidence: 99%
“…(Alhassan, et al 2006) The sugars found in these chains are also found in many other bacteria such as Pseudomonas aeruginosa, Escherichia freundii, Pneumococcu, Proteus mirabilis and Bacillus. (Barker, et al 1961;Barker, et al 1966;Barrow and Wheat 1972;Barry and Roark 1964;Benzing, et al 1981;Beynon et al 1992;Cifonelli, et al 1966;Dabrowski, et al 1996;Daniel, et al 1972;Daoust, et al 1981;Dmitriev 1980) Building these oligosaccharides will help to discover what other bacteria have these similar monosacharides or oligosaccharide chains. The initial goal was to design the building blocks of the sugars found in the cell wall polysaccharides of S. aureus type 5 and type 8.…”
Section: Introductionmentioning
confidence: 99%